If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6 + -4x) = 25 + -9x (6 * 2 + -4x * 2) = 25 + -9x (12 + -8x) = 25 + -9x Solving 12 + -8x = 25 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 12 + -8x + 9x = 25 + -9x + 9x Combine like terms: -8x + 9x = 1x 12 + 1x = 25 + -9x + 9x Combine like terms: -9x + 9x = 0 12 + 1x = 25 + 0 12 + 1x = 25 Add '-12' to each side of the equation. 12 + -12 + 1x = 25 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = 25 + -12 1x = 25 + -12 Combine like terms: 25 + -12 = 13 1x = 13 Divide each side by '1'. x = 13 Simplifying x = 13
| 6p-4(3-2p)=5(p-4)-10 | | 4(2y-1)=-8(.5-y) | | 5x+-2=8 | | 3(x-1)=3x+3-2x | | 15x-2y=16 | | 9m-14=-18 | | 3y-12-y=4(2-y) | | 2v+5=-10 | | -4x+6=.5(x+30) | | 4x^2-3x=0 | | -4+6=.5(x+30) | | 10+20x=100+25x | | (a+c)+8= | | 256x=144x | | h-45=-39 | | -4+1=13 | | 70x+900=60x+5400 | | h-48=-39 | | 2(5+6m)+16=26 | | -10y+12-2-12x-10x+11y= | | 0=14t+26 | | 5+2x+8x-8y+3y-8y= | | 4(8+5n)=172 | | -3x+2yi=15-4i | | 12-x=19 | | -5s-13=-68 | | 12w+15w-9+5=-3w+5-9 | | 7a+4=-17 | | 3x+3y=-6 | | 9-x=2 | | 4-3-5x+7x+12x-4y= | | -4y-3=1 |